Sunday
March 26, 2017

Post a New Question

Posted by on .

i think i do something wrong again(2x+1)/(x-3)-(4x-1)/(2x-3) = 0

(2x-3)(2x+1)-(4x-1) = (0)(x-3)(2x-3)

4x^2+2x-6x-3-4x-1 = 2x^2-3x-6x+9

4x^2-4 = 2x^2-3x-6x+9
-2x^2-9x+13

i put this in quadratic formula and i think it wrong becaue i get 9/2 and 0for x and it have to be 2/3.

  • math-calculus - ,

    Your first line should have been

    (2x-3)(2x+1)-(4x-1)(x-3) = (0)(x-3)(2x-3)
    4x^2 - 4x - 3 - (4x^2 -13x + 3) = 0
    4x^2 - 4x - 3 - 4x^2 + 13x - 3 = 0
    9x = 6
    x = 6/9 = 2/3

  • math-calculus - ,

    thank you very much reiny :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question